Pengaruh Perubahan Diameter dan Jumlah Lilitan Kawat Tembaga terhadap Tegangan dan Temperatur Stator Coil Sepeda Motor - Ahmad Azus Azhar Fathoni; Khambali Khambali (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
Adding too many electrical components to a vehicle can cause a lack of electrical energy. To overcome this, the capacity of the charging system needs to be improved. One method is by changing the diameter and number of turns of the copper wire in the stator coil. This study tested various combinations of wire diameter and turns to examine their effects on the voltage and temperature produced by the stator coil. The test used wire diameters of 0.7 mm, 0.9 mm, and 1.1 mm, with 50, 60, and 70 turns, at a constant engine speed of 3000 RPM for 5 minutes. The lowest voltage was recorded with a 0.7 mm diameter and 50 turns 26.5 V at the start and 25.7 V at the end. The highest voltage came from the 1.1 mm diameter with 70 turns 51 V at the start and 48.6 V at the end. The starting temperature for all variations was 36 °C. The lowest end temperature was 47.3 °C (0.7 mm, 50 turns), and the highest was 48.8 °C (1.1 mm, 70 turns). The results show that increasing both diameter and the number of turns raises voltage output, while temperature also increases slightly.